1933
DOI: 10.1042/bj0270351
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diet on the plasma-phosphatase of sheep

Abstract: RECENT work on the role of phosphatase has made it clear that the enzyme is closely concerned in the metabolism of calcium and phosphorus and in bone formation. Thus, it has been shown that an increased plasma-phosphatase content accompanies certain bone diseases in human beings [Kay, 1930], that a rise in value also occurs during the healing of fractures [McKeown and Ostergren, 1931], and that, during the healing of rickets in children, the phosphatase values are still abnormally high even after the serum-Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
3
0

Year Published

1935
1935
1979
1979

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Comparing the serum phosphatase levels in pregnant and non-pregnant cows in Table 8, it is noted that there is a higher proportion of low values among the non-pregnant cows and that the scatter of values is wider among the pregnant cows, suggesting at first sight a tendency towards higher serum phosphatase values in pregnancy. Our data, therefore, are more in line with those of Vermehren [1939] on women than with .those of Wilson & Hart [1932] and Auchinachie & Emslie [1933] on cattle and sheep.. It must, however, be admitted that our data are not sufficiently extensive to preclude the possibility of a decrease in serum phosphatase in late pregnancy such as was suggested by the results of Auchinachie & Emslie [1933] on six cows sampled during the fifth and eighth months of pregnancy.…”
Section: ~8supporting
confidence: 88%
See 2 more Smart Citations
“…Comparing the serum phosphatase levels in pregnant and non-pregnant cows in Table 8, it is noted that there is a higher proportion of low values among the non-pregnant cows and that the scatter of values is wider among the pregnant cows, suggesting at first sight a tendency towards higher serum phosphatase values in pregnancy. Our data, therefore, are more in line with those of Vermehren [1939] on women than with .those of Wilson & Hart [1932] and Auchinachie & Emslie [1933] on cattle and sheep.. It must, however, be admitted that our data are not sufficiently extensive to preclude the possibility of a decrease in serum phosphatase in late pregnancy such as was suggested by the results of Auchinachie & Emslie [1933] on six cows sampled during the fifth and eighth months of pregnancy.…”
Section: ~8supporting
confidence: 88%
“…Our data, therefore, are more in line with those of Vermehren [1939] on women than with .those of Wilson & Hart [1932] and Auchinachie & Emslie [1933] on cattle and sheep.. It must, however, be admitted that our data are not sufficiently extensive to preclude the possibility of a decrease in serum phosphatase in late pregnancy such as was suggested by the results of Auchinachie & Emslie [1933] on six cows sampled during the fifth and eighth months of pregnancy. The data given in the last three colu'mns of Table 8 do not suggest the existence of any pronounced relation between stage of pregnancy and.…”
Section: ~8supporting
confidence: 88%
See 1 more Smart Citation
“…In contrast to this the behaviour of the skeleton, in response to deficiencies or experimental interference with organic functions, is much more constant from species to species, and attention is thus strongly directed towards species differences in the structure, mechanics and functions of the gastrointestinal tract and to factors influencing absorption. In spite of the differences between sheep and non-ruminants no study, along classical lines of nutritional research, of the Ca, P and vitamin D interrelations of this species has been reported except those of Auchinachie & Fraser (1932) and Auchinachie & Emslie (1933). In these investigations the procedures used, although well suited to the problems under study, did not allow an extensive interpretation of the results to answer conclusively certain fundamental questions of relations between Ca, P and vitamin D that have already been clarified for other species.…”
mentioning
confidence: 99%
“…I know of only one blood constituent the level of which gives pre-symptomatic indication of disordered metabolism, that is the phosphatase content. It has been shown that abnormally high phosphatase levels, even without clinical evidence, are an indication of impending breakdown in metabolism of calcium and phosphorus [11]. The amounts of blood required for this test are, unfortunately, too large for the test to be feasible in clinics.…”
mentioning
confidence: 99%